ANALISIS NILAI GIZI HASIL FERMENTASI LARUTAN GULA AREN MENGGUNAKAN TERATAI SALJU (Saussurea involucrata) - Sulistiani, Widya Sartika (Universitas Tanjungpura, 2015)
The nutrition level of fermented palm sugar solution using snow lotus (Saussurea involucrata) has been analyzed. It is necessary to determine it before this product is consumed by public. Palm sugar solution had been fermented using snow lotus (Saussurea involucrata) for 72 hour. The palm sugar solution before and after fermentation was analyzed its nutrition level such as protein, carbohydrates, vitamin C and alcohol level (methanol and ethanol) based on MUI and BPOM. After fermentation the level of protein, carbohydrates, vitamin C with consecutive is 0.557%; 1.81 mg/kg and 5.71 mg/kg. The level of protein content increased by 55 % and 42 % for carbohydrates, but the level of vitamin C decreased 16% when it compared to palm sugar solution before fermentation. Methanol wasn’t detected in fermented product after 72 hour, while ethanol is still below the threshold set by the MUI and Badan POM is 0.8%, so it is safe for consumption. Keywords : Fermented, palm sugar solution.